Mexico: Women lead the way in saving the mangroves - Alejandro Castro (The UNESCO Courier, 2023)
Since she was a small child, Erika Barnett, from the Seri community in northeastern Mexico, watched mangrove seedlings be carried away by the waves. She would then gather young shoots to take back to her home on the coast.